THEORY OF NORMAL syndrome and PLUS-decoding - V. A. Lipnitski; A. O. Aliaksiuk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of the study are not primitive BCH codes with decoding the guide, the potential is much greater than the design possibilities. The efficiency of automorphisms of codes, norms theory syndromes in the correction of all admissible-Mykh minimum distances errors in the above code is shown.